St. Augustinegrass for Florida Lawns - Laurie E. Trenholm; J. Bryan Unruh; Travis W. Shaddox (EDIS, 2017)
This 10-page fact sheet is a revision that updates fertilizer rates and soil testing information. These changes align this document with other EDIS publications containing similar fertilizer information. Written by L. E. Trenholm, J. B. Unruh, and T.W. Shaddox, and publsihed by the Department of Environmental Horticulture, September 2017.